Phylogeography and reproductive isolation of the brown mussel, Perna perna, on the South African coastline - Barker, Cassandra (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Maintenance of a species' abundance and adaptive potential is partially dependent on its genetic diversity. Distinct genetic lineages within a species can differ significantly in their resistance and resilience to environmental pressure. An assessment of such differences is key to grasp the adaptive potential of a species. Physical environmental conditions are significant determinants of the distribution of species and their genetic lineages. Under climate change scenarios, the assessment of the temporal stability of the spatial distribution of genetic structure has important consequences for conservation as it offers key insights into the adaptive potential and evolutionary capacity of a species. This thesis investigated the phylogeography and reproductive isolation of Perna perna, the brown mussel. This species is an ecologically and economically important intertidal mussel on South Africa's coastline. It was determined in 2007 that there were two distinct genetic lineages of P. perna present on South Africa's coastline, the Eastern and Western lineage. This thesis compared mitochondrial DNA between samples collected in 2007 and samples collected in 2019 to determine differences in genetic structure of P. perna over time. This thesis further investigated the reproductive timing of the two lineages to determine if this contributes to the maintenance of the genetic structure of this species. The results show that there is a shift in the distribution of the Eastern lineage since 2007, an increase in the range of the overlap region, and there was a change in genetic diversity in the form of private haplotypes between 2007 and 2019. The lineages have unsynchronised spawning and reproductive patterns are more closely linked to changes in temperature. While the lineages have shown slight distributional changes over time, the influence of environmental conditions and the predicted changes in sea surface temperatures could see a change in future populations' fitness and dispersal. Thus, changes in sea surface temperature could affect reproductive timing and the future genetic stability of the species.
Keywords: Mexilhao mussel -- South Africa; Phylogeography -- South Africa; Mexilhao mussel Reproduction; Mexilhao mussel Genetics; Intertidal organisms -- South Africa; Mexilhao mussel Climatic factors -- South Africa; Cytochrome oxidase; Mitochondrial DNA; Haplotype network